2017
DOI: 10.1002/chem.201702471
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Arene‐Forming Aldol Condensation: Catalyst‐Controlled Synthesis of Axially Chiral Compounds

Abstract: The fundamental role that aldol chemistry adopts in various disciplines, such as stereoselective catalysis or the biosynthesis of aromatic polyketides, illustrates its exceptional versatility. On the one hand, numerous aldol addition reactions reliably transfer the stereochemical information from catalysts into various valuable products. On the other hand, countless aromatic polyketide natural products are produced by an ingenious biosynthetic machinery based on arene-forming aldol condensations. With the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 72 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Our previous efforts were engaged in polyketide cyclizations of artificial aldehyde substrates with pre‐organizing aromatic moieties . The mild substrate preparation and the observed control over increasingly complex substrates thereby indicated the feasibility of small‐molecule catalyzed, divergent cyclizations of native polyketides, if the reactivity and selectivity requirements are met.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous efforts were engaged in polyketide cyclizations of artificial aldehyde substrates with pre‐organizing aromatic moieties . The mild substrate preparation and the observed control over increasingly complex substrates thereby indicated the feasibility of small‐molecule catalyzed, divergent cyclizations of native polyketides, if the reactivity and selectivity requirements are met.…”
Section: Methodsmentioning
confidence: 99%
“…These cyclization studies [44][45][46][47][48][49] revealed the ability of smallmolecule catalysts to trigger polyketide-type cyclizations and suggested that also noncanonical polyketide cyclizations, that are related to the conversion of poly-β-carbonyl compounds by the polyketide synthase machineries, could be feasible. of substrates to examine this hypothesis involved the preparation of cinnamyl biindene precursors which were accessed through an oxidative dimerization or a Suzuki crosscoupling strategy.…”
Section: Synthesis Of Enantioenriched Tetra-ortho-33'-substituted Bimentioning
confidence: 99%
“…Our group focused on the development of atroposelective areneforming aldol condensations, which were inspired by the biosynthesis of aromatic polyketides. [44,45] The amine catalyzed aldol methodology was found to be broadly applicable permitting the preparation of binaphthalene carbaldehydes, [46] configurationally stable oligo-1,2-naphthylenes [47] , axially chiral amides [48] and the stereodivergent synthesis of atropisomeric multi-axis systems. [49]…”
Section: Stereoselective Synthesis Of Atropisomersmentioning
confidence: 99%
“…The 1,8‐substitution pattern at the naphthalene bridging units employed here is expected to provide only weak through‐bond electronic coupling, and it seems plausible that the overall charge‐transfer pathway includes a mixture of through‐bond and through‐space interactions. Long‐range ET across oligo‐naphthalene structures is yet far less well explored than across oligo‐ p ‐phenylenes, and the insights gained here point to uncommon phenomena that deserve further attention in future studies, particularly in view of recent advances in the synthesis of oligo‐naphthalenes . The comparatively rigid and sterically congested molecular structures resulting from the naphthalene bridges used herein are rather uncommon for ET systems, and they provide access to a multitude of charge‐transfer pathways including σ‐, π‐ and through‐space interactions.…”
Section: Figurementioning
confidence: 99%